PENELUSURAN IDENTITAS BUDAYA NUSANTARA DALAM TEKS BERBAHASA INGGRIS - Ina Sukaesih; Yoyok Sabar Waluyo; Rd Safrina (Epigram, 2019)
AbstractThis paper addresses the English translation of specific Sundanese cultural references in the English Translation of selected Sundanese short stories. The issue of translatability is highlighted as the paper explores the nuances of possible meanings from the selected words. The content analysis on Watson’s English translations of selected Sundanese short stories in “Neng Maya” is framed by theoretical propositions from Molina & Albir’s translation techniques and Nababan’s translation quality assessment. Using the methods of Spradley procedure, it is revealed that the language units found in the source texts re words and phrases, while in the target texts, clauses are also found. The types of cultural words exist in the short stories are: words of emphasis, verbs, nouns, and adverbs. The translation techniques mostly used are deletion, equivalence, modulation, reinforcement, literal, and amplification. The techniques used by the translator have led to lack of translation quality, specifically the accuracy aspect.Key words: cultural references, translatability, translation techniques, translation qualityAbstrakPaper ini menyampaikan hasil penelitian tentang penerjemahan ungkapan bermuatan budaya dari beberapa cerita pendek berbahasa Sunda dalam bahasa Inggris. Masalah ‘intranslatability’ disoroti berdasarkan eksplorasi kemungkinan nuansa makna dari kata-kata yang dipilih. Analisis konten terhadap terjemahan cerita pendek dari kumpulan cerita pendek ‘Neng Maya’ yang dikerjakan oleh C.W. Watson merujuk pada teori teknik penerjemahan yang diusulkan Molina&Albir dan teori Asesmen kualitas terjemahan dari Nababn dkk. Dengan menggunakan tahapan prosedur Spradley, dalam cerita pendek yang dipilih, terdapat beberapa tipe ungkapan bermuatan budaya, yaitu: kata penegas, kata kerja, kata benda, dan kata keterangan. Sementara unit Bahasa yang digunakan dalam teks sumber adalah kata dan frasa dan dalam teks sasaran kata, frasa dan klausas. Teknik penerjemahan yang dominan digunakan adalah deletion, equivalence, modulation, reinforcement, literal, dan amplification. Penggunaan teknik yang didominasi dengan deletion menyebabkan kurangnya kualitas terjemahan, khususnya keakuratan.Kata Kunci: ungkapan bermuatan budaya, translabilitas, teknik penerjemahan, kualitas terjemahan.